DESIGN OF MICROSTRIP PATCH ANTENNA FOR HIGH FREQUENCY APPLICATIONS - muddukrishnamanaidu, G.; priyanka, M.S (International Journal of Psychosocial Rehabilitation, 2020)
This paper represents the design of microstrip patch antenna for ultra wideband application. Ultra wide band frequency finds a wide range of use in medical applications. Microwave medical application is one of the significant features in UWB application. Microstrip antennas are preferred to be used in medical applications because of their position of safety, conformal, light weight, and simple creation. The microstrippatch is the narrow bandwidth antenna in order to use it for wide band application certain methods has to be incorporated into the design. The design methods will create directeffect onthethunderousrecurrence of the microstrip radio wire. The bandwidth modification methods used are reduction in ground plane, slotted ground plane and T and E patch. By using this method resonant frequency can be achieved up to 9GHZ. Return loss, VSWR and radiation pattern are the parameters to beanalysed.